The Utilization of Online Learning on Islamic Religious Education Subjects During the Covid-19 Pandemic at SMPN Kelumbayan Barat Tanggamus - fidian abron; Syaiful Anwar; Chairul Anwar (Journal of Research in Islamic Education, 2021)
This study aims to: (1) Determine the application of E-learning or Online in Islamic Religious Education (PAI) learning during the pandemic. (2) Measuring how effective E-learning media is on student learning at SMP N 1 Kelumbayan Barat. This research is a field research. Data was collected by conducting observations, interviews, and documentation. The data was collected by reducing the data that was arranged systematically and then displaying the data in the form of a long descriptive description and finally giving a conclusion. The results of the research are: (1) The application of e-learning in PAI learning at SMP N 1 Kelumbayan Barat is not optimal, there are many obstacles faced by teachers and students. (2) The application of e-learning in PAI learning is only a few media namely whatsapp group, google classroom, google meet, which indeed of these three are relatively light and effective to be applied there.